Impact of Behavioral and Psychological Symptoms on Caregiver Burden in Patients With Dementia With Lewy Bodies - Kanemoto, Hideki; Sato, Shunsuke; Satake, Yuto; Koizumi, Fuyuki; Taomoto, Daiki; Kanda, Atsushi; Wada, Tamiki; Yoshiyama, Kenji; Ikeda, Manabu (Frontiers in Psychiatry, 2021)
Background/Objective: Behavioral and psychological symptoms of dementia (BPSD) have been reported to affect caregiver burden in patients with dementia with Lewy bodies (DLB). However, the factor structure of BPSD and the factors that affect caregiver burden in DLB remain unknown. This study sought to classify BPSD and to reveal what type of BPSD affects caregiver burden in patients with DLB. Methods: We collected data on neuropsychiatric inventory-plus (NPI-plus), Zarit Burden Interview (ZBI), Mini-Mental State Examination (MMSE), Lawton's Instrumental Activities of Daily Living and Physical Self-Maintenance Scale (IADL/PSMS), age, and sex of 102 patients with probable DLB. An exploratory factor analysis of 13 items of the NPI-plus was carried out to classify BPSD. Multivariate regression analyses were conducted to extract the clinical variables related to caregiver burden, including factors resulting from the aforementioned factor analysis. Results: The mean age and MMSE score were 78.6 (5.6) and 20.2 (5.2), respectively. Factor analysis revealed four factors of “psychosis,” “affection,” “wakefulness,” and “hyperactivity.” “Psychosis” and “affection” factors as well as MMSE, IADL, and PSMS were significantly associated with ZBI. Multivariate regression analyses revealed that the total score of ZBI was associated with “psychosis,” “affection,” and IADL, that the personal strain score of ZBI was associated with “affection” and IADL, and that the role strain score of ZBI was associated with “wakefulness” and IADL. Conclusions: BPSD in DLB consists of three factors common to Alzheimer's disease and a specific “wakefulness” factor. In addition to IADL, each BPSD factor would affect caregiver burden in different ways in DLB.